EVALUATION OF THE OPERATIONAL CHARACTERISTICS OF X-RAY EQUIPMENT - Damir A. Zaredinov; Marina V. Li (Central Asian Journal of Medicine, 2024)
The article is devoted to the quality control of the operational characteristics of modern general-purpose X-ray machines, which are a key element in the radiation protection of patients exposed to this type of medical exposure. The work was carried out by the research and testing radiological laboratory of the Center for the Development of Professional Qualifications of Medical Workers of the Ministry of Health of the Republic of Uzbekistan. For the study, 3 medical institutions in Tashkent were selected. Laboratory specialists tested the accuracy of the anode voltage setting, the reproducibility and constancy of the anode voltage setting on the X-ray tube, the total filtration, the radiation quality, the reproducibility and constancy of the output dose at a constant setting, the linearity and duration of exposure of the X-ray machines under study.